FAKTOR-FAKTOR YANG MEMPENGARUHI OPTIMALISASI PEMANFAATAN ASET TETAP - Pamfilia Ferdinanda Montayop; Westim Ratang; Arius Kambu (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2016)
This article examines determinants which influence the optimization of fixed assets utilization in Local Treasury and Asset Management Agency of Boven Digoel Regency. The number of population in this study was 77 respondents from government officials and no… The final respondents were 69. A purpose sampling technique was used to select the respondents. A direct survey was employed to collect research data. This study used multiple regressions to empirically test the hypotheses. The findings indicated that assets inventory positively influence fixed assets utilization and management in Boven Digoel Regency. This infers that the improvements of assets inventory are likely to optimize fixed assets utilization and management in Boven Digoel Regency. In addition, legal audit was positively associated with fixed assets utilization and management. In other words, legal audit advancement is likely to optimize fixed assets utilization and management in the Regency. Moreover, assets recognition was also positively associated with fixed assets utilization and management in the Regency. This means that the better the assets recognition, the better the optimization of fixed assets utilization and management in Boven Digoel Regency. Keywords: Asset Inventory, Legal Audit, Asset Recognition, Asset Optimization.